The power of platforms—precarity and place - Davies, Anna (My University, 2023)
The expanding scale and scope of digital platforms in our lives seem undeniable as they restructure commerce, communication, work, finance, popular culture, and private and public services. However, despite their ubiquity in our lives, platforms’ relationship to increasing inequality and precarity and its implications for places, democracies and civil society remains underexplored. Kenney and Zysman (2020) consider the concentrated power of digital platforms arguing that regional scholars have failed to examine the implications of key internet platforms ‘connecting massive numbers of users/customers with service providers, advertisers or other users’. Some of these firms create profit by selling a commodity, but many others sell labour, capital and attention within the nation-state or globally (Christophers 2020). Kenney and Zysman (2020) call on researchers to study how platforms wield power, paying particular attention to how the practices of platforms impact on the spatial organization of the economy.
PUBLISHED
Keywords: Market power; Inequality; Precarity; Platform economy; Digital platforms; ECONOMIC-GEOGRAPHY; Urban Geography; human geography